Modified quadrupole mass analyzer RGA-100 for beam plasma research in forevacuum pressure range; Review of Scientific Instruments; Vol. 86, iss. 12 - Zolotukhin D. V.; Tyunkov A. V. Andrey Vladimirovich; Yushkov Y. G. Yuri Georgievich; Oks E. M. (2015, 2015)
Title screen